SYNTHESIS, CHARACTERIZATION, ANTIOXIDENT AND ANTICANCER HUMAN STUDIES OF NEW METAL ION COMPLEXES OF POLY SCHIFF BASE DERIVED FROM 4-AMINOACETOPHENONE WITH SALICYLALDEHYDE AND 4-BROMOANILINE - Al-sahlanee, Tamara Q.m; Ha Al-amery, Mohammed (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: New metal ion complexes of some transition metal ions [Cu(II), Cr(III), Cd(II), Zn(II), and VO(II)] of prepared ligand 2-(((4-(1-((4-bromophenyl) imino)ethyl) phenyl) imino) methyl) phenol were synthesized. Methods: The method is based on Schiff bases reaction of 4-aminoacetophenone with salicylaldehyde and P-bromoaniline. Results: The structures of the new metal ion complexes were characterized by elemental microanalysis (C.H.N), Fourier transform infrared, ultra violet-visible spectra, thermal gravimetric analysis-differential thermal gravimetric, flame atomic absorption, molar conductivity, magnetic susceptibility measurement, and mass spectra. According to the obtained data, the probable coordination geometries of these complexes were suggested as octahedral excepted C5 was pyramidal. All complexes were found to be non-electrolyte. Conclusion: The anticancer activity was screened against human cancer cell such brain cancer cells (AMJM), cervical cancer cells (HeLa), ovarian cancer cells (SKOV-3), and breast cancer cells (MCF-7). The results indicate that the metal ion complexes show increase cytotoxicity in proliferation to cell lines as compared to the free ligand. Antioxidant activities were shown the ligand, and their complexes have high reactivity. Â